Smelting process of special as-cast zinc alloy
Through the smelting process of special cast zinc alloys, the problems of inaccurate control of zinc alloy components and poor melt uniformity are solved, high-performance production of alloys is achieved, and strict requirements in high-end applications are met.
Patent Information
- Application Number
- CN202411533012.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The composition control of existing zinc alloys is inaccurate, poor melt uniformity, and unstable casting performance, making it difficult to meet the strict requirements for alloy performance in high-end applications.
Using the smelting process of special cast zinc alloys, small pieces such as magnesium element, zinc-titanium intermediate alloy, aluminum-silicon intermediate alloy, copper-zinc intermediate alloy and aluminum and zinc intermediate alloy are reasonably arranged in a vacuum induction smelting furnace, and control The melting rate and mixing degree of different metals, and the power control in segments and precise control of the melting temperature, reduce the presence of oxygen, form a protective atmosphere, and ensure the purity and performance of the alloy.
It realizes precise control of alloy composition and uniform melt, improves the mechanical properties of the alloy, such as hardness, tensile strength, and makes the final product have better comprehensive performance and meets the high-end fields of aerospace, automobile manufacturing, electronic products, etc. Performance zinc alloy casting requirements.
Smart Images

Figure CN119464800A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc alloys, and in particular to a smelting process of a special cast zinc alloy. Background Art
[0002] As one of the lightest metal structural materials in practical applications, zinc alloy has received extensive attention and application in various high-end application fields due to its series of excellent properties. The advantages of zinc alloy mainly include low density, high specific strength, high specific elastic modulus, good damping performance and excellent corrosion resistance, which makes it show great potential in aerospace, automobile manufacturing, electronic products and other fields. For example, its application in the automobile manufacturing industry, with the global emphasis on environmental protection and energy efficiency, automobile lightweighting has become one of the main trends in the development of the industry. By reducing the weight of the vehicle, it can significantly improve fuel efficiency and reduce carbon dioxide emissions, thereby meeting more stringent environmental regulations. Zinc alloy is particularly suitable for manufacturing various structural parts of automobiles, such as engine brackets, door inner panels, seat frames, etc., due to its excellent mechanical properties and low density. In addition, zinc alloy also has good casting properties and can be precisely formed, which makes it particularly suitable for manufacturing complex-shaped automotive parts. However, with the demand for higher performance, the performance limits of existing zinc alloys have gradually emerged. For example, mechanical properties such as hardness still need further improvement and optimization. Therefore, developing new alloy compositions and smelting processes to improve the application performance of zinc alloys in complex and harsh environments has become an important direction of current materials science research. For example, in the application number CN202311565502.4, a preparation method of a composite porous zinc alloy for bone repair is disclosed, which needs to be stirred to varying degrees in steps one, two, and three. During the smelting process, stirring will accelerate the contact between the melt and oxygen in the air, especially when oxygen is not completely isolated, which may lead to the formation of oxides on the surface or inside of the melt, affecting the purity and final performance of the material. At the same time, its processing time is too long, the process flow is relatively complicated, and the efficiency is low, which is not conducive to the industrialization and large-scale production of such zinc alloys. For another example, in the application number CN202210942121.2, a high-efficiency degassing and deslagging method for zinc alloy smelting is disclosed, which puts the raw material Zn into a vacuum smelting furnace for melting, and sequentially adds the raw materials Cu, Al, and Mg into the vacuum smelting furnace for melting to obtain a zinc alloy liquid, and its various raw materials are not well cut and size controlled, and the melting rate and mixing degree of different metals cannot be well controlled. Due to the different melting points of various metals, it is not conducive to preheating and smooth collapse of materials. Summary of the invention
[0003] In view of the above shortcomings of the prior art, the present invention provides a smelting process of a special cast zinc alloy to solve the problems of inaccurate composition control, poor melt uniformity, unstable casting performance, and difficulty in meeting the strict requirements of high-end application fields for alloy performance in the traditional smelting process. Through the smelting process of the present invention, fine control of the alloy composition and smelting process is achieved, and the mechanical properties of the alloy such as hardness and tensile strength are improved, so that the final product has better comprehensive performance, meeting the needs of aerospace, automobile manufacturing, electronic products and other fields for high-performance zinc alloy castings.
[0004] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0005] A smelting process for a special cast zinc alloy, the smelting process comprising the following steps:
[0006] S1: After drying small blocks of magnesium, zinc-titanium master alloy, aluminum-silicon master alloy and copper-zinc master alloy, the small blocks are placed at the bottom of the crucible, and large blocks of aluminum and zinc are placed on top of the small blocks, and then the crucible is placed in a vacuum induction melting furnace; in the present application, magnesium, zinc-titanium alloy, aluminum-silicon alloy and copper-zinc alloy are cut into small blocks, while aluminum and zinc remain in larger block forms, so as to better control the melting rate and mixing degree of different metals during the smelting process, and facilitate preheating and smooth collapse of materials; further, through the reasonable arrangement of materials of different specifications and sizes, the heat transfer of the melt is effectively utilized, and the large block materials on the upper layer are preheated, making it easier to melt and mix with the bottom materials, thereby improving the uniformity and quality of the alloy.
[0007] S2: After the furnace is closed, evacuate to -0.1MPa, then fill with inert gas and control the pressure in the vacuum induction melting furnace to 0.02-0.04MPa; the present application can effectively reduce the presence of oxygen during the smelting process by reducing the air pressure in the furnace, avoid oxidation reaction between metal materials and oxygen, and thus ensure the purity and performance of the alloy. In addition, when an inert gas such as argon is filled into the smelting furnace, it forms a protective atmosphere that isolates residual oxygen and other active gases, thereby preventing the metal from oxidizing at high temperatures. This approach not only further reduces the residual oxygen, but also stabilizes the air pressure in the furnace under a vacuum environment, providing good atmosphere conditions for subsequent heating and smelting.
[0008] S3: Controlling the power of the vacuum induction melting furnace in sections, first increasing the power to raise the temperature in the furnace to a certain melting temperature; when there is a sign of gas volatilization on the surface of the zinc alloy melt, then starting to reduce the power to reduce the temperature in the furnace to a relatively stable melting temperature state;
[0009] S4: When the smelting in step S3 is completed, the power of the vacuum induction melting furnace is adjusted to 0KW. After natural cooling for a certain period of time, the power is increased again, and electromagnetic stirring is continuously performed while heating is continued to complete the refining operation. During the refining operation of the present invention, electromagnetic stirring is continuously performed while heating is continued to enhance the mixing effect inside the melt, ensure that the alloy elements in the molten state can be fully and evenly distributed, and prevent the occurrence of component segregation.
[0010] S5: Complete the casting operation in the vacuum induction melting furnace, control the casting temperature to 500±20°C, cool for a certain period of time after the casting is completed, and obtain the special cast zinc alloy. The entire casting process of this application is still completed in a vacuum induction melting furnace, and the casting temperature is maintained at around 500°C. At this time, the melt has good fluidity and can quickly fill the mold while avoiding excessive gas volatilization or excessive melt fluidity caused by excessive temperature. Finally, after the casting is completed, the cooling time is controlled to ensure that the casting forms a dense and stable internal structure during the slow and uniform cooling process, thereby improving the structural stability of the zinc alloy and ultimately obtaining high-performance zinc alloy castings.
[0011] As a preferred technical solution, the special cast zinc alloy material is composed of the following components in weight percentage: aluminum 6.1% to 8.3%, copper 5.7% to 5.85%, silicon 0.3% to 0.6%, titanium 0.25% to 0.45%, magnesium 0.01% to 0.03%, iron ≤0.05%, lead ≤0.004%, cadmium ≤0.003%, tin ≤0.002%, and the balance is zinc.
[0012] As a preferred technical solution, the special cast zinc alloy material is composed of the following components in weight percentage: aluminum 6.1% to 6.3%, copper 5.7% to 5.85%, silicon 0.45% to 0.55%, titanium 0.25% to 0.35%, magnesium 0.01% to 0.03%, iron ≤0.05%, lead ≤0.004%, cadmium ≤0.003%, tin ≤0.002%, and the balance is zinc.
[0013] As a preferred technical solution, the special cast zinc alloy material is composed of the following components in weight percentage: aluminum 8.1% to 8.3%, copper 5.7% to 5.85%, silicon 0.45% to 0.55%, titanium 0.25% to 0.35%, magnesium 0.01% to 0.03%, iron ≤0.05%, lead ≤0.004%, cadmium ≤0.003%, tin ≤0.002%, and the balance is zinc.
[0014] As a preferred technical solution, the size of the small block is limited to 10*10*5mm, and the length, width and height of the large block are limited to 5 to 6 times the length, width and height of the small block respectively.
[0015] As a preferred technical solution, the zinc-titanium master alloy is Zn-0.5Ti, the aluminum-silicon master alloy is Al-20Si, and the copper-zinc master alloy is Cu-25Zn. The inventors of the present application have found that during the smelting process, the addition of Si and Ti elements is crucial to the block cutting process of the master alloys Zn-0.5Ti, Al-20Si and Cu-25Zn. In order to ensure that the high melting point master alloy can be fully melted, the master alloy needs to be cut into small pieces within 10*10*5mm. The selection of this size can not only accelerate the melting of the high melting point alloy, but also avoid smelting failure caused by uneven heating. Since Zn-0.5Ti and Al-20Si have relatively high melting points, a reasonable placement order is crucial. In order to prevent excessive volatilization of zinc during the smelting process, further, first place the Zn-0.5Ti and Al-20Si small pieces at the bottom of the crucible, which helps them to evenly heat up during preheating and reduce volatilization losses. Then place the Cu-25Zn small piece with a relatively low melting point in the middle. This layered placement not only helps to ensure the reasonable distribution of temperature gradients, but also effectively prevents the rapid volatilization of zinc at high temperatures. For the remaining large blocks of pure Zn and pure Al, their length, width and height are limited to 5 to 6 times the length, width and height of the small blocks, respectively. This size can ensure that they can be smoothly placed in the crucible, and can also ensure that they are fully mixed with other intermediate alloy materials during the smelting process, preventing incomplete melting or excessive volatilization due to oversize. The appearance shape of the small blocks and large blocks of the present invention is not strictly limited, and can be selected from at least one of a sphere, a cuboid, a cube, a cylinder, etc. For ease of placement, a cuboid is preferred.
[0016] As a preferred technical solution, in step S3, the first stage power is increased from 0KW to 3-7KW, the temperature is raised to 300-400℃, and the heating is continued for a certain period of time; the second stage power is increased from 3-7KW to 10-15KW, the melting temperature is controlled at 600-700℃, and when there are signs of gas volatilization on the surface of the zinc alloy melt, the power is appropriately lowered to 3-7KW to continue melting, and the temperature is lowered to 300-400℃, and the melting time is less than the heating time of the first stage power. The vacuum induction melting furnace of the present application induces current inside the metal through the alternating electromagnetic field generated by the induction coil, thereby generating heat and melting the metal. As a more preferred technical solution, at the beginning of smelting, the first stage power of the vacuum induction melting furnace is gradually increased from 0KW to 5KW, and the heating is continued for 10 minutes to ensure that the material can gradually heat up and reduce the local overheating caused by too fast heating; the second stage power is increased from 5KW to 10KW, and the melting temperature is controlled at 600-700℃. By continuously adjusting the heating power, the composition balance of the melt is maintained. When the gas volatilization phenomenon is observed in the vacuum induction melting furnace through the eyepiece, it indicates that the material has reached the boiling point of zinc. The power is reduced to 5KW and the melting is uniformly carried out for 5 minutes to prevent excessive zinc evaporation, thereby maintaining the composition balance of the melt. After the smelting is completed, the power is reduced to 0KW, and the melt is allowed to cool in the crucible for 10 minutes without any external intervention to ensure the natural homogenization of the internal structure of the melt. In this process, the temperature change is closely monitored by the temperature sensor to ensure that each metal material can be fully melted and mixed with each other to form a uniform alloy melt.
[0017] As a preferred technical solution, in step S4, the natural cooling time is controlled at 5 to 10 minutes, the power is increased to 3 to 7 kW again, the refining operation time is controlled at 1 to 2 minutes, and the melt temperature is controlled to be stable at 600 to 700°C during the refining operation.
[0018] As a preferred technical solution, in step S4, the refining operation also uses argon blowing, and high-purity argon is introduced into the melt to promote the dissolved gas and inclusions in the melt to float up and be discharged. By using argon blowing, the impact and stirring of argon promote the dissolved gas and inclusions in the melt to float up and be discharged, effectively removing inclusions and homogenizing the melt composition. This process continuously performs electromagnetic stirring and uniform heating to ensure that the temperature inside and outside the melt is consistent and the melt composition is uniform.
[0019] As a preferred technical solution, the Vickers hardness of the special cast zinc alloy material is greater than or equal to 130HV, and the tensile strength is greater than or equal to 265Mpa.
[0020] Beneficial effects of the present invention:
[0021] The smelting process of the special cast zinc alloy of the present invention realizes the precise control of alloy composition and the homogenization of alloy melt by innovatively optimizing the size of different metal raw materials, controlling the power in sections and precisely controlling the smelting temperature during the smelting process. Furthermore, by adding silicon (Si) and titanium (Ti) to the alloy, this process not only realizes the precise control of the melting rate and mixing degree of different metals, but also promotes the homogenization of the melt, thereby improving the uniformity and quality of the alloy. The addition of silicon and titanium helps to form the strengthening phase TiSi2, which is evenly distributed on the interface of the α+η eutectoid structure, effectively refines the alloy matrix structure, and improves the hardness and tensile strength of the alloy. In addition, by rationally arranging materials of different specifications and sizes, effectively utilizing the heat transfer of the melt, preheating the upper bulk material, making it easier to melt and mix with the bottom material, thereby further enhancing the mechanical properties of the alloy, such as hardness and tensile strength, while maintaining the casting performance of the alloy. This design helps to improve the reliability and durability of the alloy in high-end application fields.
[0022] In general, the smelting process of the special cast zinc alloy of the present invention not only has excellent mechanical properties, but also achieves high production efficiency and low energy consumption by precisely controlling the smelting conditions and raw material processing. The optimized addition of silicon and titanium further improves the hardness of the alloy, so that the alloy exhibits excellent comprehensive performance in the application of aerospace, automobile manufacturing, electronic products and other fields, and meets the strict requirements for high-performance zinc alloy castings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the process flow of Example 1 of the present invention.
[0024] Figure 2 a and 2b are photos of the high temperature box-type resistance furnace and vacuum induction melting furnace, respectively.
[0025] Figure 3 a, 3b, 3c and 3d are raw material photos of Zn, Cu-25Zn, Zn-0.5Ti and Al-20Si, respectively.
[0026] Figure 4 4a and 4b are hardness comparison diagrams and tensile strength comparison diagrams of the zinc alloys of Example 1, Example 2 and Comparative Example 1 of the present invention, respectively.
[0027] Figure 5 This is the surface morphology of the commercial alloy AlCuZinc5 of Comparative Example 1 of the present invention.
[0028] Figure 6 This is the EDS energy spectrum of the commercial alloy AlCuZinc5 of Comparative Example 1 of the present invention.
[0029] Figure 7This is the surface morphology and energy spectrum analysis diagram of the special cast zinc alloy in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0031] Example 1
[0032] The smelting process of the special cast zinc alloy in this embodiment is as follows: Figure 1 As shown, it specifically includes the following steps:
[0033] S1: Dry small pieces of magnesium, Zn-0.5Ti, Al-20Si and Cu-25Zn (length, width and height are 10*10*5mm) and put them into the bottom of an alumina crucible, then place large pieces of aluminum and zinc (length, width and height are 60*60*30mm) on top of the small pieces, and then place the alumina crucible in a vacuum induction melting furnace. Figure 2 The high temperature box-shaped resistance furnace (SRJX-8-13) shown in a is used to dry and dehydrate the single substance Ti at a temperature of 400°C and a drying time of 4 hours to ensure that the smelted intermediate alloy Zn-0.5Ti has a high alloy purity. In addition, the Cu-25Zn intermediate alloy is also dried at a temperature of 200°C and a drying time of 4 hours. The photos of the smelting raw materials Zn, Cu-25Zn, Zn-0.5Ti and Al-20Si are shown in Figure 1. Figure 3 Specifically, the raw material components used in this embodiment are shown in Table 1: Table 1 Raw material composition:
[0034] S2: After the furnace is closed, the vacuum is evacuated to -0.1 MPa, and then an inert gas is filled in and the vacuum induction melting furnace (such as Figure 2 The pressure in the furnace (shown in b) is 0.03MPa.
[0035] S3: Controlling the power of the vacuum induction melting furnace in sections, first increasing the power to raise the temperature in the furnace to a certain melting temperature; when signs of gas volatilization appear on the surface of the zinc alloy melt, then starting to reduce the power to reduce the temperature in the furnace to a relatively stable melting temperature state.
[0036] In step S3, the power of the first stage is increased from 0KW to 5KW, the temperature is raised to 350°C, and the heating is continued for 10 minutes; the power of the second stage is increased from 5KW to 10KW, and the melting temperature is controlled at 650°C. When there is a sign of gas volatilization on the surface of the zinc alloy melt, the power is appropriately lowered to 5KW to continue melting, and the temperature is lowered to 350°C, and the melting time is continued for 5 minutes.
[0037] S4: When the smelting in step S3 is completed, the power of the vacuum induction melting furnace is adjusted to 0KW. After natural cooling for 10 minutes, the power is increased to 5KW again, and electromagnetic stirring is continued while heating to complete the refining operation. The refining operation time is 2 minutes. The refining operation process controls the melt temperature to be stable at 650°C. The refining operation process also adopts argon blowing, and high-purity argon gas is introduced into the melt to promote the dissolved gas and inclusions in the melt to float up and be discharged.
[0038] S5: Complete the casting operation in the vacuum induction melting furnace, control the casting temperature to 500°C, cool for 20 minutes after the casting is completed, and obtain the special cast zinc alloy, which is abbreviated as 8Al-5.8Cu-0.3Ti-0.4Si zinc alloy. The special cast zinc alloy material is composed of the following components in weight percentage: 8% aluminum, 5.8% copper, 0.4% silicon, 0.3% titanium, 0.02% magnesium, 0.03% iron, 0.002% lead, 0.003% cadmium, 0.001% tin, and the balance is zinc.
[0039] The special cast zinc alloy material obtained by melting in this embodiment is subjected to primary cutting and high-speed wire cutting to obtain a zinc alloy sheet with a wall thickness of 5 mm; the test results show that its Vickers hardness is 143.3 HV and the tensile strength is 272.2 MPa.
[0040] In addition, after the entire smelting process, the slag is significantly reduced, indicating that the size control and reasonable placement order of the master alloy greatly improve the smelting efficiency. Especially for the high-melting-point strengthening elements Si and Ti, this process ensures that they can be evenly distributed in the zinc alloy matrix while reducing the volatilization of the low-melting-point Zn element. The composition of the alloy finally smelted is strictly controlled, and its composition fluctuation is kept within a reasonable error range, ensuring the quality of the material.
[0041] Comparative Example 1
[0042] The zinc alloy of this comparative example is a commercial zinc alloy AlCuZinc5, which is composed of the following components in weight percentage: 2.8% aluminum, 5.6% copper, 0.04% magnesium, 0.03% iron, 0.002% lead, 0.003% cadmium, 0.001% tin, and the balance is zinc.
[0043] Under the same test conditions, the test results show that its Vickers hardness is 127.6HV and the tensile strength is 253Mpa.
[0044] Example 2
[0045] The smelting process of the special cast zinc alloy in this embodiment, its raw material composition and smelting steps are basically the same as those in Example 1, except that in the smelting process of this embodiment, the special cast zinc alloy material is composed of the following components in weight percentage: 6% aluminum, 5.8% copper, 0.4% silicon, 0.3% titanium, 0.02% magnesium, 0.03% iron, 0.002% lead, 0.003% cadmium, 0.001% tin, and the balance is zinc. It is abbreviated as 6Al-5.8Cu-0.3Ti-0.4Si zinc alloy.
[0046] Under the same test conditions, the test results show that its Vickers hardness is 132.92HV and the tensile strength is 266.8Mpa.
[0047] In order to further analyze the strengthening mechanism of Si and Ti elements on the mechanical properties and hardness of zinc alloys, the inventors first conducted microscopic experimental characterization on the cast AlCuZinc5 alloy (Comparative Example 1) formed in the same furnace. Figure 5 As shown in the figure, the surface morphology of AlCuZinc5 after etching shows a relatively coarse tree-like structure, and three distinct structures can be observed. In order to further analyze the composition of the cast AlCuZinc5 alloy phase, Figure 6 a EDS surface scan and point scan were performed, such as Figure 6 As shown in Figures 6b, 6c and 6d, combined with the data in Table 2, it is obvious that the coarse dendritic phase is mainly composed of Cu and Zn. Through the analysis of Point1 scan, the dendritic phase is determined to be CuZn4 phase, and a trace amount of Al-rich phase is observed near CuZn4. Through the analysis of Point2 scan, the Al-rich phase is mainly composed of (η+α)+η+CuZn4 eutectic structure. Point3 scan shows that the relatively smooth surface is the matrix phase, and the (η+α)+η+CuZn4 eutectic structure is concentrated at the junction of CuZn4 and the matrix phase. In general, the cast AlCuZinc5 alloy is mainly composed of CuZn4, (η+α)+η+CuZn4 eutectic structure, and matrix phase. Table 2 EDS scanning element content of AlCuZinc5 alloy
[0048] In order to further explore the distribution of Si and Ti elements in the zinc alloy, SEM and EDS analysis were performed on the special cast zinc alloy of Example 2. The Si element was added through the Al-20Si master alloy, such as Figure 7As shown in Figure a, the microstructure of the 6Al-5.8Cu-0.3Ti-0.4Si zinc alloy has changed. A small amount of small irregular black structures are found in the matrix and the (α+η)+η eutectic structure. Gray irregular phases are observed near the black particles. The dendritic strengthening phase CuZn4 has not changed significantly. In order to further analyze the distribution and composition of Si and Ti elements in 6Al-5.8Cu-0.3Ti-0.4Si, Figure 7 b EDS surface scan was performed. Figure 7 The EDS energy spectra of Si and Ti in c and 7d and the point scanning results in Table 3 show that the black irregular structure is Si element. The Si in 6Al-5.8Cu-0.3Ti-0.4Si zinc alloy mainly exists in the form of elemental Si. The elemental Si is distributed in granular form on the interface of α+η eutectoid structure, which plays a certain role in refining the α+η eutectoid structure. Moreover, the elemental free Si does not precipitate on the original strengthening phase CuZn4 of the zinc alloy. The lighter color is the strengthening phase TiSi2. The elemental Si and TiSi2 are co-distributed on the interface of α+η eutectoid structure. From the comprehensive analysis of mechanical properties, hardness and microscopic characterization, the main reason why the hardness of 6Al-5.8Cu-0.3Ti-0.4Si zinc alloy is greater than that of cast AlCuZinc5 is that the existence of elemental Si and the formation of strengthening phase TiSi2 between Si and Ti strengthen the zinc alloy matrix and improve the overall hardness of the zinc alloy. In general, through Figure 7 It can be seen that Si and Ti elements are evenly distributed in the zinc alloy without enrichment. This result further verifies the effectiveness of this process in improving the performance of zinc alloys and ensures the comprehensive properties of zinc alloys such as tensile strength and hardness. Table 3 EDS scanning element content of 6Al-5.8Cu-0.3Ti-0.4Si alloy
[0049] In general, if Figure 4 a and Figure 4 As shown in b, the hardness of the special cast zinc alloy in Example 1 of the present application is increased by 12.3% in Vickers hardness and 7.6% in tensile strength compared with the existing commercial zinc alloy AlCuZinc5 (Comparative Example 1); the hardness of the special cast zinc alloy in Example 2 of the present application is increased by 4.2% in Vickers hardness and 5.5% in tensile strength compared with the existing commercial zinc alloy AlCuZinc5 (Comparative Example 1).
[0050] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention claimed.
Claims
1. A smelting process for a special cast zinc alloy, characterized in that: The smelting process comprises the following steps: S1: Drying small blocks of magnesium, zinc-titanium master alloy, aluminum-silicon master alloy and copper-zinc master alloy and placing them at the bottom of a crucible, placing large blocks of aluminum and zinc on top of the small blocks, and then placing the crucible in a vacuum induction melting furnace; S2: After the furnace is closed, the vacuum is evacuated to -0.1 MPa, and then an inert gas is filled in and the pressure in the vacuum induction melting furnace is controlled to be 0.02-0.04 MPa; S3: Controlling the power of the vacuum induction melting furnace in sections, first increasing the power to raise the temperature in the furnace to a certain melting temperature; when there is a sign of gas volatilization on the surface of the zinc alloy melt, then starting to reduce the power to reduce the temperature in the furnace to a relatively stable melting temperature state; S4: When the smelting in step S3 is completed, the power of the vacuum induction melting furnace is adjusted to 0 kW, and after natural cooling for a certain period of time, the power is increased again, and electromagnetic stirring is continuously performed while heating to complete the refining operation; S5: completing the casting operation in the vacuum induction melting furnace, controlling the casting temperature to be 500±20° C., cooling for a certain period of time after the casting is completed, and obtaining the special cast zinc alloy.
2. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: The special cast zinc alloy material is composed of the following components in percentage by weight: 6.1% to 8.3% aluminum, 5.7% to 5.85% copper, 0.3% to 0.6% silicon, 0.25% to 0.45% titanium, 0.01% to 0.03% magnesium, ≤0.05% iron, ≤0.004% lead, ≤0.003% cadmium, ≤0.002% tin, and the balance is zinc.
3. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: The special cast zinc alloy material is composed of the following components in percentage by weight: 6.1% to 6.3% aluminum, 5.7% to 5.85% copper, 0.45% to 0.55% silicon, 0.25% to 0.35% titanium, 0.01% to 0.03% magnesium, ≤0.05% iron, ≤0.004% lead, ≤0.003% cadmium, ≤0.002% tin, and the balance is zinc.
4. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: The special cast zinc alloy material is composed of the following components in percentage by weight: 8.1% to 8.3% aluminum, 5.7% to 5.85% copper, 0.45% to 0.55% silicon, 0.25% to 0.35% titanium, 0.01% to 0.03% magnesium, ≤0.05% iron, ≤0.004% lead, ≤0.003% cadmium, ≤0.002% tin, and the balance is zinc.
5. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: The size of the small block is limited to 10*10*5mm, and the length, width and height of the large block are limited to 5 to 6 times of the length, width and height of the small block respectively.
6. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: The zinc-titanium master alloy is Zn-0.5Ti, the aluminum-silicon master alloy is Al-20Si, and the copper-zinc master alloy is Cu-25Zn.
7. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: In step S3, the power of the first stage is increased from 0KW to 3-7KW, the temperature is raised to 300-400°C, and the heating is continued for a certain time; the power of the second stage is increased from 3-7KW to 10-15KW, the melting temperature is controlled at 600-700°C, and when there are signs of gas volatilization on the surface of the zinc alloy melt, the power is appropriately lowered to 3-7KW to continue melting, and the temperature is lowered to 300-400°C, and the melting time is less than the heating time of the first stage power.
8. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: In step S4, the natural cooling time is controlled within 5 to 10 minutes, the power is increased to 3 to 7 kW again, the refining operation time is controlled within 1 to 2 minutes, and the melt temperature is controlled to be stable at 600 to 700°C during the refining operation.
9. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: In step S4, the refining operation also uses argon blowing, and high-purity argon is introduced into the melt to promote the dissolved gas and inclusions in the melt to float up and be discharged.
10. The smelting process of the special cast zinc alloy according to claim 1, characterized in that: The special cast zinc alloy material has a Vickers hardness greater than or equal to 130 HV, and a tensile strength greater than or equal to 265 MPa.
Citation Information
Patent Citations
Efficient degassing and deslagging method for zinc alloy smelting
CN115287480A
Preparation method of composite structure porous zinc alloy for bone repair
CN117564274A
Cited By
Smelting process of high-toughness zinc alloy
CN120796755A